Surviving Death - Johnston, Mark, 1954- (Book collections on Project MUSE., 2010)
Johnston presents an argument for a form of immortality that divests the notion of any supernatural elements. The book is packed with illuminating philosophical reflection on the question of what we are, and what it is for us to persist over time.